2005
DOI: 10.1111/j.1471-4159.2005.03365.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism of exogenous pyruvate

Abstract: Pyruvate given in large doses may be neuroprotective in stroke, but it is not known to what degree the brain metabolizes pyruvate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 44 publications
(97 reference statements)
4
67
0
Order By: Relevance
“…Its elevation in the brain signals cerebral ischemic damage. 30 However, lactate and pyruvate can readily cross the blood-brain barrier and enter the tricarboxylic acid cycle, 31,32 being preferential oxidative energy substrates over glucose for neurons. 33,34 The beneficial effect of exogenous glucose, lactate, and pyruvate has been shown in some TBI models, [35][36][37] but these substrates only modestly reduce the lesion size, with no apparent functional protection in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Its elevation in the brain signals cerebral ischemic damage. 30 However, lactate and pyruvate can readily cross the blood-brain barrier and enter the tricarboxylic acid cycle, 31,32 being preferential oxidative energy substrates over glucose for neurons. 33,34 The beneficial effect of exogenous glucose, lactate, and pyruvate has been shown in some TBI models, [35][36][37] but these substrates only modestly reduce the lesion size, with no apparent functional protection in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids were analyzed by high-performance liquid chromatography (HPLC) and fluorescence detection after precolumn derivatization with o-phthaldialdehyde, using an 1100 series HPLC unit (Agilent), as described previously. 9 Supernatants of brain abscess pus were analyzed by reflectance spectrophotometry for glucose and lactate as described previously, 17 and pH was measured with a pH meter (inoLab pH 7110, WTW GmbH) that was calibrated before each reading.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…It has been shown that overexpression of MnSOD, 0.5-2 fold, can attenuate kainate induced seizures, however animals with diminished MnSOD levels showed an exacerbation of kainate-induced seizure and hippocampal damage, which was attenuated with antioxidant treatment (Patel, 2002). Overexpression of MnSOD also produces lower amounts of inactive aconitase and 8-hydroxy-2-deoxyguanosine (8-OHdG), measures of oxidative protein and DNA (most likely mtDNA) damage, indicating a role in the preservation of mitochondrial function (Gonzalez, et al, 2005, Patel, 2002, Sleven, et al, 2006. Damage to mitochondrial complex I, α-keto-glutarate dehydrogenase, citrate synthase, aconitase, and GSH can be detected at time points well after the end of an epileptic episode, and damage to these cellular components can induce cell death cascades and increase the likelihood of future seizures .…”
Section: Antioxidative Mechanismsmentioning
confidence: 99%